2009
DOI: 10.2165/00002018-200932040-00005
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines and Guillain-Barré Syndrome

Abstract: Guillain-Barré syndrome (GBS) is the leading cause of acute flaccid paralysis in developed countries and is characterized by various degrees of weakness, sensory abnormalities and autonomic dysfunction. Although the underlying aetiology and pathophysiology of GBS are not completely understood, it is broadly believed that immune stimulation plays a role in its pathogenesis. Thus, since vaccines have an effect on the immune system it is biologically plausible that immunizations may be associated with subsequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
171
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(179 citation statements)
references
References 67 publications
3
171
1
4
Order By: Relevance
“…Although an association between the influenza virus vaccine and GBS was observed in 1976 (23), assessment of current pH1N1 vaccines had found either no association or a higher rate of GBS with 0.85 per million vaccine doses in our study, which is consistent with estimates for seasonal influenza virus vaccine. This rate is also lower than the baseline incidence rate of 0.6 to 1.9 cases per 1 million population in European countries or the estimated risk of 1 case per 1 million doses of seasonal influenza virus vaccines given in the United States (24,25).…”
Section: Discussionmentioning
confidence: 68%
“…Although an association between the influenza virus vaccine and GBS was observed in 1976 (23), assessment of current pH1N1 vaccines had found either no association or a higher rate of GBS with 0.85 per million vaccine doses in our study, which is consistent with estimates for seasonal influenza virus vaccine. This rate is also lower than the baseline incidence rate of 0.6 to 1.9 cases per 1 million population in European countries or the estimated risk of 1 case per 1 million doses of seasonal influenza virus vaccines given in the United States (24,25).…”
Section: Discussionmentioning
confidence: 68%
“…Although infrequent, it also may happen as a neurologic adverse event following immunization. The pathophysiology of vaccination-related GBS is not completely understood and probably an immune stimulation plays a role in its pathogenesis 1,3 . Recent studies showed no conclusive result proving a causal relationship between influenza A vaccine and GBS, nor a possible increased risk for GBS after H1N1 imunnization 4,5 .…”
Section: Casementioning
confidence: 99%
“…Guillain-Barré syndrome (GBS) has been described as adverse event following different types of vaccines, such as influenza, varicella, polio virus and hepatitis B 1 . Since 2009 with the emergence of the pandemic H1N1 influenza virus infection in humans, new vaccines have been developed for influenza A (H1N1) as a preventive strategy to reduce transmission, protect groups at increased risk of infection, and decrease complications and death 2 .…”
mentioning
confidence: 99%
“…Il en va de la responsabilité de chaque soignant de bien comprendre les enjeux de la vaccination, vis-à-vis de lui-même, de son entourage, et de ses patients [6]. Les populations prioritaires ont été définies par le gouvernement (circulaire du 28 octobre 2009) après avis du Haut conseil de santé publique [7] et sont les suivantes, par ordre décroissant de hiérarchisation : -personnel de santé de réanimation néonatale et pédiatrique, -personnels médical, paramédical et aide-soignant des établissements de santé, ainsi que médecins et infirmier(e)s du secteur ambulatoire exposés à des patients grippés ou en contact avec des patients porteurs de facteurs de risque, -femmes enceintes à partir du deuxième trimestre, -entourage des nourrissons de moins de 6 mois (famille et personnes assurant la garde de ces nourrissons), -professionnels chargés de l'accueil de la petite enfance (jusqu'à 3 ans), -nourrissons âgés de 6 à 23 mois révolus avec facteurs de risque (atteints de pathologies chroniques sévères), -sujets âgés de 2 à 64 ans avec facteurs de risque, -autres professionnels de santé, personnels de la chaîne de secours et transporteurs sanitaires, -nourrissons âgés de 6 à 23 mois révolus sans facteurs de risque, ou leur entourage si le vaccin non adjuvé est indisponible, -personnels d'accueil des pharmacies, -personnels des établissements médico-sociaux, Cependant, aucun lien épidémiologique n'a été mis en évidence [11,12]. On peut rappeler à cette occasion que le syndrome de Guillain-Barré a une incidence de 2,8 cas pour 100 000 habitants en population générale, et de 4 à 7 pour 1 000 000 habitants après une grippe naturelle.…”
Section: La Vaccination Anti-a/(h1n1)2009vunclassified